A by‐product of swine slaughtering as a protein source in broiler diets: effects on performance, composition of excreta, litter quality and on foot pad health. (19th June 2017) - Kölln, M.; Loi‐Brügger, A.; Kamphues, J.
Summary: Foot pad dermatitis (FPD) is of great concern in poultry industry, and dietary strategies are needed to improve foot pad health because of animal welfare and economic reasons. As the main factor for the development of FPD is the DM content of litter (consisting mainly of excreta; Kamphues et al., 2011), there are different dietary approaches to influence this disease pattern. In two consecutive trials, a total of 200 broilers were kept from day 7 until the 35th day of life. They were divided into four groups at each trial and fed with one of four experimental diets, based on wheat and corn mainly, but differing in the protein source: Group 1 was fed a diet with soya bean meal (SBM) as the main protein source, whereas Group 2, Group 3 and Group 4 were assigned to diets with 4, 8 and 12% of a protein‐rich (66.7% CP in DM) by‐product of swine slaughtering [Swine Protein Meal (SPM); in exchange for SBM]. The inclusion of 12% SPM resulted in a decreased dietary potassium content of about 3 g/kg diet (Group 1 vs. 4). Increasing dietary levels of the by‐product (8 and 12%) led to lowered feed intake (Group 1 vs. 4: ~10%) and weight gain (Group 1 vs. Group 4: ~8.5%). Although highest DM contents of excreta and litter were determined in Group 4, foot pad health was not influenced positively as hypothesized. Remarkable was the observed 'stickiness' of excreta when the by‐product was included in the diet at increasing levels, presumably due to the high proportion of bones in the by‐product. In conclusion, substituting SBM by 4% of the by‐product of swine slaughtering in broiler diets did not impair performance parameters, but led to the most favourable foot pad scores in this study.